Variations in apparent diffusion coefficient values following chemotherapy in pediatric neuroblastoma - Senay Demir; Naime Altinkaya; Nazim Emrah Kocer; Ayse Erbay; Pelin Oguzkurt (Diagnostic and Interventional Radiology, 2015)

(untitled)
PURPOSEIn children the assessment of solid tumors’ response to chemotherapy is based primarily on size reduction, which can be unreliable and a late marker, in the presence of necrosis. We aimed to establish whether apparent diffusion coefficient (ADC) values of childhood neuroblastomas show proportional changes in relation to chemotherapy response.METHODSWe evaluated 15 pediatric patients with abdominopelvic neuroblastomas, who had undergone MRI before and after chemotherapy. Two radiologists retrospectively analyzed all images by drawing a round uniform region-of-interest in the solid/contrast-enhancing portion of the lesions in consensus. The ADC values from pre- and postchemotherapy images were compared.RESULTSPostchemotherapy ADC values were significantly higher than those obtained before treatment (P < 0.05, for minimum, maximum, and median ADC values).CONCLUSIONOur results support diffusion-weighted MRI as a promising noninvasive biomarker of therapeutic responses. To the best of our knowledge, this is the first report to compare diffusion- weighted imaging findings before and after chemotherapy in childhood neuroblastic tumors.